Different Violence, Different Justice? Taking Structural Violence Seriously in Post-Conflict and Transitional Justice Processes - Dáire McGill (State Crime, 2017)
Structural violence is a central, yet neglected, problem in post-conflict and transitional societies owing to the circumscribed sphere of action within which dominant processes generally operate. This article analyses the potential of transitional justice to reduce structural violence, finding many of its mechanisms limited in this regard. In response, I argue for the necessity of an alternative transformative justice approach that pays more attention to the historical and socioeconomic underpinnings of armed conflict, and critical analyses of the prevailing social structures and power relations on which it is founded. Conceptualizing transformative justice as the most comprehensive stop on a transitional justice continuum ensures that these issues are taken seriously without discarding the field's existing expertise. I operationalize transformative justice by creating an innovative structural violence reduction matrix that interrogates the diagnostic, process and outcome dimensions of initiatives undertaken in transitional contexts.